Description of Potential PTSD in Students Surviving COVID-19 at the Faculty of Medicine, Andalas University - Annisa Aulia; Arina Widya Murni; Yulistini; Yaslinda Yaunin; Mustafa Noer; Taufik Ashal (Sumatera Medical Journal, 2025)
Background: The COVID-19 pandemic has become a potentially traumatic event that can trigger the development of Post-Traumatic Stress Disorder (PTSD), especially in COVID-19 survivors. The study found that college students (aged 16 to 25 years) are at the most significantly risk for exposure to potentially traumatic events. Objective: To describe the potential for PTSD in students who survived COVID-19 at the Faculty of Medicine, Andalas University. Methods: This research is a descriptive study with a case-control design. A total of 167 student survivors of COVID-19 participate in the study. Data were obtained by the PTSD Checklist for DSM-5 (PCL-5) questionnaire digitally. Results: The study found that 18% of COVID-19 survivor students at the Faculty of Medicine, Andalas University had the potential to experience PTSD. The potential for PTSD is more susceptible to being experienced by male COVID-19 survivor students (30.4%), younger age, and experienced clinical symptoms of moderate illness COVID-19 (29,2%). Alterations in mood and cognition symptoms domain are the most dominant symptoms of PTSD experienced by study subjects with potential PTSD. Conclusion: Most study subjects with potential PTSD don’t experience stressors like life-threatening events, exposure to news about COVID-19, or social isolation.